Art-based education and political-economic discourse: some examples (Praxis Educativa, 2019)
This paper analyzes the representation of the economy through contemporary art and, consequently, the educational potential of this particular tool. The work reviews some examples of works by some contemporary artists whose interest focuses on various economic issues of our time. The work explores the possibilities that art offers for the reflection on economic problems..
Keywords: art-based education; economic policy; contemporary art; economic problems; innovation in teaching and learning